Reason for the Family Doing Confinement on People with Mental Disorders - Nining Wuri Lestari; Setyawati Soeharto; Heni Dwi Windarwati (GoAcademica Research & Publishing, 2020)
The number of retention is still high in Indonesia to find out the reasons for the family doing confinement on people with mental disorders in Trenggalek Regency. This research is a qualitative with an interpretative phenomenological approach. Data were obtained through in-depth interviews with twelve families who treated people with post-pasung mental disorders in Trenggalek Regency. Data analysis using IPA (Interpretative Phenomenological Analysis), obtained four themes namely feeling frustrated with the patient's condition, feeling annoyed because of the patient's disobedience, the helplessness of the family doing something, bored because there is no meaningful development in the patient the family put up on people with mental disorders because they feel frustrated and helpless to face the patient's condition.